2002
DOI: 10.1080/02656730210146908
|View full text |Cite
|
Sign up to set email alerts
|

Radiosensitization of heat resistant human tumour cells by 1 hour at 41.1°C and its effect on DNA repair

Abstract: The present study was undertaken to determine if short duration (1-2 h), moderate hyperthermia (41.1 degrees C) could radiosensitize human tumour cells. It was found that moderate hyperthermia (41.1 degrees C), for as little as 1 h, can radiosensitize heat resistant human adenocarcinoma cells, NSY42129 (NSY), provided the cells are irradiated 15 min prior to the end of the heat exposure. Analysis of the survival data showed a 2.5-3-fold increase in the alpha parameter with no significant change in the beta par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
44
0
1

Year Published

2003
2003
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(50 citation statements)
references
References 47 publications
5
44
0
1
Order By: Relevance
“…Translocation of the Mre11 DSB repair protein from the nucleus to the cytoplasm has also been implicated (106,111). However, disappearance of Mre11 protein foci at the sites of irradiation-induced DNA DSBs was not observed by pre-incubation of cells at 41˚C (24,27).…”
Section: Discussionmentioning
confidence: 97%
“…Translocation of the Mre11 DSB repair protein from the nucleus to the cytoplasm has also been implicated (106,111). However, disappearance of Mre11 protein foci at the sites of irradiation-induced DNA DSBs was not observed by pre-incubation of cells at 41˚C (24,27).…”
Section: Discussionmentioning
confidence: 97%
“…The employment of heat, as a fundamental component of this new therapeutic methodology, is justified by its own cancericidal property and chemosensitivity-modulating capacity. The biophysical effects of hyperthermia are not completely understood, but probably include membrane protein denaturation, increased vascular permeability [18,19], alterations in multimolecular complexes such as the insulin receptor [20] and in the cytoskeleton [18], and changes in enzyme complexes for DNA synthesis and repair [21]. Moreover, the architecture of the vasculature in solid tumors is chaotic, resulting in regions with low pH, hypoxia, and low glucose level [22].…”
Section: Discussionmentioning
confidence: 99%
“…Recently it was demonstrated that the BRCA-2 protein is transiently inhibited by mild hyperthermia (Krawzcyk et al, 2011). Also translocation of the Mre11 DSB repair protein from the nucleus to the cytoplasm has been implicated (Xu et al, 2002(Xu et al, , 2007. However, disappearance of Mre11 protein foci at the sites of irradiation induced DNA double strand breaks by 41ºC pre-incubation of cells was not observed (Krawzcyk et al, 2011;Bergs, 2007a).…”
Section: Discussionmentioning
confidence: 99%
“…In a study by Xu et al (1999) 41.1C pre-treatment of cells for 1h did not induce radiosensitization whereas treatment for 2h or more resulted in radiosensitization, in the hyperthermia resistant, but not in the hyperthermia sensitive cell line (Xu et al, 1999]. However, simultaneous treatment of the sensitive cell line with 1h 41.1C hyperthermia and radiation did increase cellular radiosensitivity (Xu et al, 2002). An important mechanism of mild hyperthermia induced radiosensitization in vivo is the reoxygenation of tumors by an increase in blood flow (Vujaskovic et al, 2004;Oleson & Robertson, 1995;Song et al, 1995).…”
Section: Discussionmentioning
confidence: 99%